Clinical Efficacy of the Huo Xue Hua Yu Method Combined with Aspirin in the Treatment of Acute Cerebral Infarction: A Systematic Evaluation and Meta-analysis - Chen, Chu; Ma, Fang; Wen, Xinli; Liu, Xing; Tang, Qing; Wu, Yilun (Current Pharmaceutical Design, 2023)
Objective: The study aimed to evaluate the clinical efficacy of the Huo Xue Hua Yu method combined with aspirin in the treatment of patients with acute cerebral infarction (ACI). Methods: By searching electronic databases, such as the Chinese Biomedical Literature Database (CBM), the China National Knowledge Infrastructure Database (CNKI), the China Science and Technology Journal Database, Wanfang, PubMed, Embase, and the Cochrane Library, all randomized controlled trials (RCTs) published before 14 July, 2022, and published in Chinese or English languages were selected. Statistical analysis was performed using Review Manager 5.4 calculation software to calculate the odds ratio (OR), mean difference (MD), 95% confidence interval (CI), and p values. Results: 13 articles that included 1,243 patients were identified; in 646 of them, the Huo Xue Hua Yu method combined with aspirin has been administered, while 597 have only been administered aspirin therapy. The combined treatment significantly improved clinical efficacy (OR: 4.41, 95% CI: 2.90 to 5.84, p < 0.001, I2 = 0), as assessed by the National Institutes of Health Stroke Scale score (MD = -4.18, 95% CI: -5.69 to -2.67, p < 0.001, I2 = 94%), Barthel score (MD = -2.23, 95% CI: -2.66 to -1.81, p < 0.001, I2 = 82%), the China Stroke Scale score (MD = 6.74, 95% CI: -3.49 to 16.96, P = 0.20, I2 = 99%), packed cell volume (MD = -8.45, 95% CI: -8.81 to -8.09, p < 0.001, I2 = 98%), fibrinogen levels (MD = -0.93, 95% CI: -1.23 to -0.63, p < 0.001, I2 = 78%) and plasma viscosity (MD = -0.51, 95% CI: -0.72 to -0.30, p < 0.001, I2 = 62%). Conclusion: The combination of the Huo Xue Hua Yu method and aspirin represents a beneficial adjunctive therapy for ACI.
Keywords: disorder